Mechanics of fracture and flexure in Antarctic ice sheets and ice shelves - Zhang, H (2024)
Understanding the mass balance of the Antarctic and Greenland ice sheets is essential to make accurate projections of global sea-level rise. Beyond their mechanics as viscous fluid flows, the mass balance is influenced by fracturing, a complex and challenging aspect of glaciology. In grounding zones and floating ice shelves, ice fracturing is often associated with flexure modulated by ocean tides and subglacial water flow, as well as stresses created by shearing, such as pinning points. Fracture and flexure significantly affect the vulnerability of Antarctic ice shelves to hydrofracturing and, by altering buttressing effects, the mass balance of the entire Antarctic Ice Sheet. In this thesis, I investigate the mechanics of ice fracture and flexure, as well as their potential impact on ice sheet mass balance using mathematical modelling and geospatial data analysis. Chapter 1 provides an introduction to the context of my studies, including key topics such as sticky patches beneath grounded ice sheets and glaciers, tidally-modulated grounding line and ice--shelf calving front. In Chapter 2, I consider basal fracturing in grounded glaciers and ice sheets. Sticky patches are regions with higher basal shear stress than their surroundings. By including basal shear stresses in the classical, vertical mode-I fracture model, I model basal hydrofracturing on the ice--bedrock interface near a sticky patch. The study shows the importance of spatially varying basal conditions in promoting water-assisted crevassing on the ice--bed interface. In Antarctic grounding zones, where grounded ice sheets transition to floating ice shelves, ice experiences changing basal conditions and tidal flexure, which can promote fracturing. Meanwhile, meltwater from supraglacial lakes can provide additional stress that opens a fracture. In Chapter 3, I develop a viscoelastic marine ice sheet model and study tidal flexure together with hydrofracture propagation. The model suggests that tidal flexural stress significantly contributes to hydrofracturing in the grounding zones, and aligns well with remotely sensed data from the Amery Ice Shelf grounding zone. Tidal flexure can also be modified by subglacial hydrology. To explore the effect of subglacial hydrology on the grounding line (GL) and tidal flexure, in Chapter 4, I develop a model combining a viscoelastic ice stream and subglacial hydrology. Previous studies have examined these processes using a 2D elastic framework or 3D regional-scale ice sheet model. My model serves as an intermediate state, which makes predictions of tidal variations in velocity and provides a mechanistic understanding of the tidal flexure of an ice stream with a subglacial hydrological system. In Chapter 5, I focus on calving and flexure near the shelf edge. By using a viscoelastic flexure model, I investigate different mechanisms that cause flexure near the calving front, and how the flexure evolves due to viscous creep and leads to calving events.